2022
DOI: 10.3389/fimmu.2022.915412
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity Risk Assessment of Spontaneously Occurring Therapeutic Monoclonal Antibody Aggregates

Abstract: Aggregates of therapeutic proteins have been associated with increased immunogenicity in pre-clinical models as well as in human patients. Recent studies to understand aggregates and their immunogenicity risks use artificial stress methods to induce high levels of aggregation. These methods may be less biologically relevant in terms of their quantity than those that occur spontaneously during processing and storage. Here we describe the immunogenicity risk due to spontaneously occurring therapeutic antibody ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…13 However, artificially induced aggregates may differ from aggregates occurring spontaneously in terms of aggregate shapes and chemical modifications. 18,19 Swanson et al 20 used process-induced aggregates to investigate their immunogenic potential in vitro using peripheral blood mononuclear cells and a cell line with a reporter gene for immune activation. They found that whereas artificially induced aggregates induced both adaptive and innate immune responses, spontaneous aggregates only induced innate responses in a limited subset of donor peripheral blood mononuclear cells, suggesting that data obtained in stressed samples may not be representative for what is happening in marketed products that are used in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, artificially induced aggregates may differ from aggregates occurring spontaneously in terms of aggregate shapes and chemical modifications. 18,19 Swanson et al 20 used process-induced aggregates to investigate their immunogenic potential in vitro using peripheral blood mononuclear cells and a cell line with a reporter gene for immune activation. They found that whereas artificially induced aggregates induced both adaptive and innate immune responses, spontaneous aggregates only induced innate responses in a limited subset of donor peripheral blood mononuclear cells, suggesting that data obtained in stressed samples may not be representative for what is happening in marketed products that are used in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, artificially induced aggregates may differ from aggregates occurring spontaneously in terms of aggregate shapes and chemical modifications 18,19 . Swanson et al 20 . used process‐induced aggregates to investigate their immunogenic potential in vitro using peripheral blood mononuclear cells and a cell line with a reporter gene for immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other antibody-derived fragments, knob peptides do not rely on the β-barrel core scaffold of Ig domains but instead use disulfide bonds and a short internal β-sheet to maintain their compact structure ( 19 , 21 ). This structure may also be an advantage given the propensity of some Ig domains to aggregate and produce amyloid ( 62 66 ), which can be especially problematic in lung tissue where delivery regimes like inhalers or nebulizers can be harsh on protein molecules ( 67 ) where denatured or aggregated forms can cause immunogenicity ( 68 70 ). The compact, disulfide-bonded knob may enhance stability to proteases or heat, which would be advantageous in extreme environments in vivo, like the GI tract, or ex vivo, to enable long shelf lives or eliminate the need for cold-chain distribution of therapeutic products ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of additional clinical factors on immunogenicity is a complex area requiring further investigation. 67,68 Immunogenicity refers to the development of serum anti-drug antibodies (ADAs) that specically target and bind to the proteins of interest, such as a therapeutic proteins or drugs. This immune response can have signicant implications for the efficacy and safety of the protein products and can lead to reduced their effectiveness.…”
Section: Stability Challenges Of Proteinbased Therapymentioning
confidence: 99%